Comparative effects of stearic acid, calcium and magnesium stearates as dopants in model lipid membranes - Vashchenko, O.V.; Kasian, N.A.; Budianska, L.V. (Functional Materials, 2018)
Comparative studies are reported for calcium and magnesium stearates as well as for stearic acid introduced as dopants in model lipid membranes, both individually and in pairs with cycloserine. Membranotropic effects of the dopants were detected on the basis of complex analysis of phase transition parameters obtained by means of differential scanning calorimetry. The individual membranotropic effects increase in order: CaSt < MgSt < StA. It was established that cycloserine extends the temperature range of the membrane ripple phase, unlike the other substances studied. Joint addition of each stearate with cycloserine resulted in a previously unknown synergic membranotropic effect reflected as additional elevation of phase transition temperatures with a non-additive concentration dependence. The synergic effect grows with dopants concentration and appears more pronounced for pre-transition than for main transition. Meanwhile, no synergic effect was observed for stearic acid with cycloserine, and the joint effects could be ranged as: CaSt≥ StA ~ 0.